1999
DOI: 10.1007/s004339900044
|View full text |Cite
|
Sign up to set email alerts
|

Cellular distribution and phototoxicity of Benzoporphyrin derivative and Photofrin

Abstract: Photodynamic therapy (PDT) induces cell-membrane damage and alterations in cancer-cell adhesiveness, an important parameter in cancer metastasis. These alterations result from cell sensitivity to photosensitizers and the distribution of photosensitizers in cells. The efficacy of photosensitizers depends on their close proximity to targets and thus on their pharmacokinetics at the cellular level. We studied the cellular distribution of photosensitizers with a confocal microspectrofluorimeter by analysing the fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 25 publications
0
14
0
1
Order By: Relevance
“…For instance, photosensitizers that localized to plasma membrane, lysosome, and Golgi apparatus resulted in a different photo‐killing effect 26. Intracellular studies carried by Rousset et al has revealed stronger cytoplasmic than nuclear fluorescence for both BPD and Photofrin 27,28. Because mitochondria play a pivotal role in arbitrating apoptosis, we focused on whether the BPD‐MA can localize to the mitochondrial area by time‐lapse imaging the emitted red fluorescence of BPD‐MA after cells were loaded with BPD‐MA.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, photosensitizers that localized to plasma membrane, lysosome, and Golgi apparatus resulted in a different photo‐killing effect 26. Intracellular studies carried by Rousset et al has revealed stronger cytoplasmic than nuclear fluorescence for both BPD and Photofrin 27,28. Because mitochondria play a pivotal role in arbitrating apoptosis, we focused on whether the BPD‐MA can localize to the mitochondrial area by time‐lapse imaging the emitted red fluorescence of BPD‐MA after cells were loaded with BPD‐MA.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to apoptosis and necrosis, cell death shared with both apoptotic and necrotic characteristics, the mixed type of cell death, has also been described (Formigli et al, 2000;Denecker et al, 2001). Previous studies have pointed out the complexity of cell death induced by PDT, which can be affected by the nature of sensitizers, the dose of light energy, the incubation protocol, and the cell type (Dellinger, 1996;Chan et al, 2000;Rousset et al, 2000;Fabris et al, 2001;Wyld et al, 2001). In this report, we have analyzed the subcellular localization of Photofrin in A431 cells and characterized the Photofrin-PDT-induced cell death when plasma membranes are the main targets.…”
Section: Discussionmentioning
confidence: 94%
“…The intracellular concentrations of photosensitizers were important factors in the effectiveness of PDT. 25 Therefore, PDT requires essentially high contrast between malignant cells and surrounding normal cells as well as sufficient concentration of photosensitizer in malignant cells. On the basis of our previous studies, there were different kinetic changes of ZnPcS 2 P 2 concentration between leukemic cell lines and normal BMC.…”
Section: Discussionmentioning
confidence: 99%